Analisis Kepercayaan Diri Siswa Kelas 4 SD dalam Pembelajaran Tematik Tema 9 melalui Model Pembelajaran SAVI - Mayasya Dwi Sasmito; Melik Budiarti; Sri Lestari (Prosiding Konferensi Ilmiah Dasar, 2022)
Basically,humans are social creatures, generally humans as social beings will interact with each other. Confidence will grow from the process of interaction in the social environment and continues, this self-confidence does not just appear there is a long process and there is a very short process. This study aims to find out how the confidence of grade 4 students in thematic learning theme 9 SAVI learning model at SDN Tamanarum 1 Parang. The population in this study were 4th grade students, and the samples used were 3 students from 4th grade. This type of research uses a qualitative approach, with data collection methods using triangulation. Data analysis in this study used qualitative analysis. Based on the results of the data analysis research, it was found that the students' self-confidence in grade 4 was obtained through the SAVI learning model (Somatic, Auditory, Visual and Intellectual).